Driving with homonymous visual field loss: Does visual search performance predict hazard detection?. (February 2015) - Smith, Matthew; Mole, Callum D; Kountouriotis, Georgios K; Chisholm, Catharine; Bhakta, Bipin; Wilkie, Richard M
Introduction: Stroke often causes homonymous visual field loss, which can lead to exclusion from driving. Retention of a driving licence is sometimes possible by completing an on-road assessment, but this is not practical for all. It is important to find simple tests that can inform the assessment and rehabilitation of driving-related visual-motor function. Method: We developed novel computerised assessments: visual search; simple reaction and decision reaction to appearing pedestrians; and pedestrian detection during simulated driving. We tested 12 patients with stroke (seven left, five right field loss) and 12 controls. Results: The homonymous visual field defect group was split into adequately compensated or inadequately compensated groups based on visual search performance. The inadequately compensated group had problems with stimuli in their affected field: they tended to react more slowly than controls and in the driving task they failed to detect a number of pedestrians. In contrast, the adequately compensated group were better at detecting pedestrians, though reaction times were slightly slower than controls. Conclusion: We suggest that our search task can predict, to a limited extent, whether a person with stroke compensates for visual field loss, and may potentially identify suitability for specific rehabilitation to promote return to driving.